Bi-material topology optimization for fully coupled structural-acoustic systems with isogeometric FEM–BEM. (February 2022) - Chen, L.L.; Lian, H.; Liu, Z.; Gong, Y.; Zheng, C.J.; Bordas, S.P.A.
Abstract: This paper presents a novel method for topology optimization of vibrating structures interacted with acoustic wave for the purpose of minimizing radiated sound power level. We consider exterior acoustic fields and bi-material shell models without damping in this work. Within the isogeometric analysis framework, we employ Catmull–Clark subdivision surfaces to construct geometries and discretize physical fields. The isogeometric finite element method with Kirchhoff–Love shell elements is coupled with the isogeometric boundary element method in acoustics. The topology optimization is performed through density-based approaches, in which the sensitivities are evaluated with adjoint variable methods. Numerical experiments demonstrate the validity and effectiveness of the algorithm for topology optimization of structural-acoustic interaction systems.